Community Nurses' Strategies for Overcoming Stunting Through a Family Approach - Ari Setiawati; Fransisca B Batticaca; Evi Nurmaisa Biduri; Mery Kana; Maria Kurni Menga (Jurnal Ilmiah Kesehatan Sandi Husada)
Introduction: Stunting is a public health problem that is still high in Indonesia, especially in rural areas. This condition has a long-term impact on a child's physical growth, cognitive development, and quality of life. Community nurses have an important role to play in stunting prevention and management efforts, particularly through a more holistic and sustainable family-based approach. Research Objectives To identify and analyze the strategies used by community nurses in tackling stunting through a family approach, as well as to understand the challenges faced in implementing these strategies at the community level.